2012
DOI: 10.1007/s00381-012-1718-8
|View full text |Cite
|
Sign up to set email alerts
|

The clinical features and surgical outcomes of pediatric patients with primary spinal cord tumor

Abstract: PSCT in pediatric patients can be surgically removed with an acceptable low surgical morbidity. Progression-free survival was found to be related to the grade of tumor and the extent of tumor resection. Early diagnosis and treatment anticipate good functional neurologic outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 15 publications
3
22
0
Order By: Relevance
“…3,11,13,24 A series of publications have already reported good outcomes (using the mMS) and determined the safety and efficacy of the best possible microsurgical tumor removal with the aid of intraoperative neurophysiological monitoring. 1,2,[5][6][7][8]12,14,17,18,21,25 No significant overall impact on reported QOL can be measured using the PedsQL 4.0 when comparing children with IMSCT and a healthy collective. There is only one minor exception to this conclusion: in the physical health item of the CSR score in the low-grade subgroup (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3,11,13,24 A series of publications have already reported good outcomes (using the mMS) and determined the safety and efficacy of the best possible microsurgical tumor removal with the aid of intraoperative neurophysiological monitoring. 1,2,[5][6][7][8]12,14,17,18,21,25 No significant overall impact on reported QOL can be measured using the PedsQL 4.0 when comparing children with IMSCT and a healthy collective. There is only one minor exception to this conclusion: in the physical health item of the CSR score in the low-grade subgroup (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[1921] GTR is recommended whenever feasible. Several studies have presented that GTR improved mortality in patients who have had primary malignant spinal cord tumors, [16,18,22] while a few studies found that GTR did not have any benefit and could even be associated with higher mortality. [5,23] Since primary spinal GBMs tend to be infiltrative and there is no distinct margin between tumor and surrounding normal cord tissue, [24] a STR or biopsy that does not cause further neurological dysfunction is appropriate in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…Intradural extramedullary tumors are most commonly schwannomas, myxopapillary ependymomas, and atypical teratoid/rhabdoid tumors. Finally, an intramedullary tumor should raise suspicion for low‐grade astrocytomas, ependymomas and gangliogliomas .…”
Section: Discussionmentioning
confidence: 99%